Enhancing Computational Thinking Skills through Digital Literacy and Blended Learning: The Mediating Role of Learning Motivation - Putri Nirmala; Iwan Suhardi; Andi Baso Kaswar; Dewi Fatmarani Surianto; Muhammad Fajar B; Soeharto Soeharto; Zsolt Lavicza (Online Learning In Educational Research (OLER), 2025)
In the digital era, computational thinking becomes an essential skill to overcome technological challenges in 21st centuryeducation. This study investigates the impact of digital literacy and blended learning on computational thinking skills, focusing on the mediating role of learning motivation. A total of 413 university students from blended learning environments participated, using a structured questionnaire with validated scales for digital literacy, computational thinking, and learning motivation. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test direct and mediation relationships. The results showed that digital literacy and blended learning significantly influenced computational thinking, with learning motivation acting as a mediator that strengthened this relationship. Digital literacy showed a greater influence than blended learning. These findings highlight the importance of integrating digital literacy and motivational strategies into blended learning to optimize the development of computational thinking skills, as well as providing insights for learning design that is relevant to the needs of the 21st century.